Molecular Docking and In Silico ADMET Study Reveals Acylguanidine 7a as a Potential Inhibitor of β-Secretase. (10th April 2016) - Nisha, Chaluveelaveedu Murleedharan; Kumar, Ashwini; Nair, Prateek; Gupta, Nityasha; Silakari, Chitrangda; Tripathi, Timir; Kumar, Awanish
Abstract : Amyloidogenic pathway in Alzheimer's disease (AD) involves breakdown of APP by β -secretase followed by γ -secretase and results in formation of amyloid beta plaque. β -secretase has been a promising target for developing novel anti-Alzheimer drugs. To test different molecules for this purpose, test ligands like acylguanidine 7a, rosiglitazone, pioglitazone, and tartaric acid were docked against our target protein β -secretase enzyme retrieved from Protein Data Bank, considering MK-8931 (phase III trial, Merck) as the positive control. Docking revealed that, with respect to their free binding energy, acylguanidine 7a has the lowest binding energy followed by MK-8931 and pioglitazone and binds significantly to β -secretase. In silico ADMET predictions revealed that except tartaric acid all other compounds had minimal toxic effects and had good absorption as well as solubility characteristics. These compounds may serve as potential lead compound for developing new anti-Alzheimer drug.